2017
DOI: 10.13168/cs.2017.0041
|View full text |Cite
|
Sign up to set email alerts
|

Microstructure, Thermo-Physical, Mechanical and Wear Properties of in-Situ Formed Boron Carbide - Zirconium Diboride Composite

Abstract: Microstructure, thermos-physical, mechanical and wear properties of in-situ formed B 4 C-ZrB

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2019
2019
2020
2020

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 38 publications
0
4
0
Order By: Relevance
“…Alexander et al [10] investigated a B 4 C-carbon nanotube system and obtained a specific wear rate of 1.06 × 10 −6 mm 3 /N•m, which was lower than that of B 4 C ceramics. Murthy et al [11] added ZrO 2 to B 4 C ceramics and noted that ZrB 2 formed in situ and that sub-micron-sized round pores formed owing to the formation of CO gas could help to deflect and/or arrest cracks, improving the tribological properties of B 4 C ceramics. Among B 4 C-based composite ceramics, it has been observed that B 4 C-SiC composite ceramics showed better mechanical properties and oxidation resistance as compared to monolithic B 4 C ceramics [12][13][14].…”
Section: Introductionmentioning
confidence: 99%
“…Alexander et al [10] investigated a B 4 C-carbon nanotube system and obtained a specific wear rate of 1.06 × 10 −6 mm 3 /N•m, which was lower than that of B 4 C ceramics. Murthy et al [11] added ZrO 2 to B 4 C ceramics and noted that ZrB 2 formed in situ and that sub-micron-sized round pores formed owing to the formation of CO gas could help to deflect and/or arrest cracks, improving the tribological properties of B 4 C ceramics. Among B 4 C-based composite ceramics, it has been observed that B 4 C-SiC composite ceramics showed better mechanical properties and oxidation resistance as compared to monolithic B 4 C ceramics [12][13][14].…”
Section: Introductionmentioning
confidence: 99%
“…Transgranular lateral cracking, slip lines‐ and material removal was found in indentation and scratch grooves in all the composites and COF was also found low at all loads (5‐10 N) 133 . Wear behaviour of ZrB 2 –B 4 C composite processed via reactive hot pressing of B 4 C and ZrO 2 revealed decrease in COF with increasing load and less wear than monolithic B 4 C 134 . Wear behavior of nanoscaled (20‐60 vol%) ZrB 2 –SiC (ZS) composites prepared via polymer derived route followed by SPS was studied by Jiabei et al (2018) 138,139 .…”
Section: Relation Between Mechanical Properties and Wear Performance mentioning
confidence: 85%
“…So wear has a great role in long life functioning of these components as excessive wear of the mating components sometimes lead to catastrophic failure 122–127 . Literature survey revealed that wear performance of ZrB 2 ‐ based ceramics was studied by several researchers majorly in un lubricated (dry) conditions, wear of ceramics depend on several factors like surface roughness, contact geometry, microstructural features, grain sizes, mechanical properties, load, speed, temperature, duration, and environment 115‐116,128–134 . Erosive wear behavior of spark plasma‐sintered ZrB 2 ‐(10‐30 vol%) SiC composites against SiC erodent at varying angle of incidence (30°‐90°) at room and high (800°C) temperature revealed that increased % of SiC resulted in 68% and 78% reduction in erosive wear rate of the composite at room and high temperature, respectively 115 .…”
Section: Relation Between Mechanical Properties and Wear Performance mentioning
confidence: 99%
“…Boron carbide (B 4 C), one of the most important engineering ceramics, has been extensively used in various industrial fields of cutting tools [1], nozzles [2], astronomical applications [3], ballistic armour [4], thermal neutron detectors [5] and as an enhancing phase in alloys [6][7][8], because its special atomic structure and composition lends itself to outstanding physical and mechanical properties [9][10][11][12][13], such as a high melting point (2450 ℃), high hardness (30 ~ 45 GPa), excellent chemical inertness, low density (2.52 g•cm -3 ) and strong absorption neutron ability. Nevertheless, the high friction coefficient of B 4 C (0.4 ~ 0.9) seriously impedes its further application.…”
Section: Introductionmentioning
confidence: 99%